Pengaruh Reinforcement Terhadap Hasil Belajar Atletik Mahasiswa Olahraga - Gutoro, Tri Setyo (FKIP Universitas Lampung, 2017)
The effect of reinforcement on athletic achievement to sport students. The aim of this research is to find out influence of reinforcement to learning achievement of high jump of flop style in student collage. The type of research used experiment with the one-group pre-test post-test design. The sample in this research is the student collage of the first semester in Department of Ilmu keolahragaan FIK UNCEN. The data collection tool used the test, which is the ability test to jump high of flop style. The result of this research found that there was influence of reinforcement to learning achievement of high high jump of flop style in student collage. Keywords: reinforcement, high jump, flop styleDOI: http://dx.doi.org/10.23960/jpp.v7.i2.201701